2002
DOI: 10.1093/toxsci/67.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Abnormalities in the Rat Mammary Gland following Gestational and Lactational Exposure to 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD)

Abstract: 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) exposure during gestation has revealed reproductive anomalies in rat offspring, including inconclusive reports of stunted mammary development in females (Brown et al., 1998, Carcinogenesis 19, 1623-1629; Lewis et al., 2001, TOXICOL: Sci. 62, 46-53). The current studies were designed to examine mammary-gland development in female offspring exposed in utero and lactationally to TCDD, and to determine a critical exposure period and cellular source of these effects. Long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
137
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(149 citation statements)
references
References 44 publications
10
137
1
1
Order By: Relevance
“…Estrogens are critical to the proliferation of breast tissue and development of the mammary gland, and early age of menarche, as well as late menopause, and late age at first birth are proxies for estrogen burden and known risk factors for breast cancer. [99][100][101] Early environmental exposures that mimic estrogens, such as bisphenol A, 102 atrazine, 103 and polyaromatic hydrocarbons, 104 may be related to earlier breast development, thereby putting the rapidly proliferating mammary tissue at risk. Chemicals that are associated with early menarche, such as polybrominated biphenyls 105 and dichlorodiphenyldichloroethylene, 106 are also of interest.…”
Section: Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Estrogens are critical to the proliferation of breast tissue and development of the mammary gland, and early age of menarche, as well as late menopause, and late age at first birth are proxies for estrogen burden and known risk factors for breast cancer. [99][100][101] Early environmental exposures that mimic estrogens, such as bisphenol A, 102 atrazine, 103 and polyaromatic hydrocarbons, 104 may be related to earlier breast development, thereby putting the rapidly proliferating mammary tissue at risk. Chemicals that are associated with early menarche, such as polybrominated biphenyls 105 and dichlorodiphenyldichloroethylene, 106 are also of interest.…”
Section: Breast Cancermentioning
confidence: 99%
“…104,107,109 Toxicologic studies show that dosing with endocrinedisrupting chemicals during different periods in an animal's life produces different effects on the mammary gland and hormone levels. 102,103,110 The importance of early exposure is illustrated by data from women who were exposed to radiation from the atomic bomb in Hiroshima. Girls at highest risk for breast cancer (ninefold increased risk) were those who were aged Յ4 years at the time of the bomb blast.…”
Section: Breast Cancermentioning
confidence: 99%
“…There have been reported gross malformations of the external genitalia of female rat offspring exposed to TCDD in utero [7]. Female rats exposed perinatally to TCDD weighed significantly less than the control rats and displayed delayed vaginal opening and persistent vaginal threads [8]. Our lab has shown that prenatal TCDD treatment can have carcinogenic consequences in the mammary gland, another hormone-responsive organ.…”
Section: 378-tetrachlorodibenzo-p-dioxin (Tcdd)mentioning
confidence: 79%
“…In that study, an increased number of terminal end buds, a proliferative, immature structure that is susceptible to carcinogenesis, were observed at the time of DMBA exposure in TCDD-exposed animals, suggesting that TCDD delayed mammary gland maturation. Other investigators have noted that mammary glands taken from 4-day-old offspring exposed perinatally to TCDD had reduced primary branches, decreased epithelial elongation, and significantly fewer alveolar buds and lateral branches [8]. Though control animals developed well-differentiated terminal structures by postnatal day 68, TCDD-exposed animals retained undifferentiated terminal structures.…”
Section: 378-tetrachlorodibenzo-p-dioxin (Tcdd)mentioning
confidence: 93%
“…Rats exposed to a single dose of TCDD on gestation day 15 retained undifferentiated terminal structures on post-natal day 68 (Fenton et al, 2002). Exposure effects of dioxin include delayed proliferation and differentiation of the mammary gland as well as an elongation of the window of sensitivity to potential carcinogens (Birnbaum and Fenton, 2003).…”
Section: Dioxinmentioning
confidence: 99%